Organizational Culture and Performance-Based Compensation in Family Firms: Does Family Involvement in Management Matter? - Peláez-León, Juan David; Salas-Arbeláez, Laura; García-Solarte, Mónica (Review of Business Management, 2023)
Purpose – This study aims to analyze how different types of organizational culture influence the implementation of performance-based compensation policies in familyowned micro, small and medium-sized enterprises (MSMEs) and whether the presence of the owning family in the management of the firm moderates this relationship. Theoretical framework – Cameron and Quinn’s (2011) typology of organizational culture and empirical evidence in the family business field were used to explain the relationship between organizational culture and performance-based compensation policies. Design/methodology/approach – Hypotheses were statistically tested using a multiple hierarchical regression analysis with a cross-sectional sample of 315 family MSMEs located in three main cities in Colombia. Findings – The results obtained suggest that there is no single cultural path for implementing a performance-based compensation policy in family MSMEs, even when the presence of family members in managerial positions moderates this relationship. The clan, adhocratic, and market cultures favor using a performancebased compensation policy in family-owned MSMEs. Practical & social implications of research – Our results present organizational culture as a key driver of compensation. Researchers, managers, and consultants should consider the characteristics of the organizational culture before suggesting implementing performance-based compensation policies in family firms. Originality/value – This work contributes to the literature on human resources and family businesses by extending the existing knowledge on the relationship between organizational culture and compensation policies related to performance in family MSMEs. Furthermore, it offers empirical evidence in the Latin American context of a relationship treated mainly from a conceptual approach and in the eastern context and developed countries. Keywords: Organizational culture, HRM, performance-based compensation policy, family firms, MSMEs.